Bankruptcy of Individual Debtors Regarding Joint Assets of Husband and Wife - Shafira Hijriya; Misnar Syam (Dinasti Research, 2024)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on the Almighty Godhead. The existence of this marriage results in the union of the husband's assets with the wife's assets, which is usually known as joint assets. However, this can be waived if there is a marriage agreement before the marriage takes place. The regulation of the concept of joint property in a husband and wife marriage experiencing bankruptcy is divided into two, namely for husband and wife who are married with a marriage agreement and for husband and wife who are married with a union of assets. For bankruptcy resolution, if joint assets are insufficient to pay debts, it must be proven that the debt is a personal debt or a joint debt.